Polymeric substrates with tunable elasticity and nanoscopically controlled biomolecule presentation - Aydin, Daniel; Louban, Ilia; Perschmann, Nadine; Blümmel, Jacques; Lohmüller, Theobald; Cavalcanti-Adam, Elisabetta A.; Haas, Tobias L.; Walczak, Henning; Kessler, Horst; Fiammengo, Roberto; Spatz, Joachim P. (Langmuir, 2010)
Despite tremendous progress in recent years, nanopatterning of hydrated polymeric systems such as hydrogels still represents a major challenge. Here, we employ block copolymer nanolithography to arrange gold nanoparticles on a solid template, followed by the transfer of the pattern to a polymeric hydrogel. In the next step, these nanoparticles serve as specific anchor points for active biomolecules. We demonstrate the engineering of poly(ethylene glycol) hydrogel surfaces with respect to elasticity, nanopatterning, and functionalization with biomolecules. For the first time, biomolecule arrangement on the nanometer scale and substrate stiffness can be varied independently from each other. Young’s moduli, a measure of the compliance of the substrates, can be tuned over 4 orders of magnitude, including the values for all of the different tissues found in the human body. Structured hydrogels can be used to pattern any histidine-tagged protein as exemplified for his-protein A as an acceptor for immunoglobulin. When cell-adhesion-promoting peptide cRGDfK is selectively coupled to gold nanoparticles, the surfaces provide cues for cell−surface interaction and allow for the study of the modulation of cellular adhesion by the mechanical properties of the environment. Therefore, these substrates represent a unique multipurpose platform for studying receptor/ligand interactions with adhering cells, mechanotransduction, and cell-adhesion-dependent signaling.
Gesehen am 28.11.2022